Muslim Turcophobia: A Study of Two Missionary Authors - Murat Köylü (Cumhuriyet İlahiyat Dergisi)

(untitled)
Among Turks, major religions with universal messages have always been welcomed with tolerance. The fact that Turks generally did not convert to religions other than Islam led to the interpretation of Islam as the most suitable religion for the character and national culture of Turks, and for this reason, Turks accepted Islam voluntarily, not by force. The proximity of the Turks to the Muslim regions made it easier for them to become Muslims and they became Muslims in groups. The statement in the Qur’ānic Ayat âl -Kursi; His pulpit has encompassed the heavens and the earth كُرْسِيُّهُ السَّمٰوَاتِ وَالْاَرْضَۚ وَلَََا يَؤُ۫دُهُ حِفْظُهُمَاۚ وَهُوَ الْعَلِيُّ الْعَظ۪يمُ the similarity in the fact that Gök Tengri, which they have believed in since the beginning of their existence, is both in the sky and much closer to them (closer than their jugular veins) has facilitated the change of belief in the Turks. The seven stories of the sky, which their ancestors saw as Uçmak, the fact that hell is seven stories below the earth, free thought and tolerance in both religions and the fact that there is only one God religion. The compatibility of the belief in God with hundreds of years of customs and traditions facilitated the acceptance of the idea that Islam was a suitable religion for them. The enmity against Muslim Turks, which started in the Christian world with the progress of Turkish tribes towards the West after the adoption of Islam, has increased the efforts of fanatical missionary Christian writers to create prejudice with their publications, which are far from historical facts, to demonize Turks in the Western public opinion. The common characteristics of these writers are that they fictionalize alleged inhumane crimes against Christians and present them as if they were true, and that they unconditionally support Greeks and Armenians, whom they see as the real owners of Anatolia. In this way, they accelerated the spread of "Islamophobia" in Western public opinion, and the persecution and massacres of Muslims were ignored. However, neither the Holy Qur’ān, the Turks, nor the Prophet Muhammad deserve these accusations and slanders. However, the literature review revealed that no specific research (thesis, book, article) has been conducted on the subject. In this context, although Muslim-Turkish enmity has been used in different ways in original studies conducted by researchers, the impact of missionary activities that started especially in the 19th century and the main reasons for this enmity have not been investigated specifically by missionary writers. The publications of the two missionary authors researched in this study have not been translated into Turkish until today. As a methodology, the literature review on the impact of missionary and missionary activities on Muslim Turcophobia was applied in the form of the publications and analysis of the missionary authors taken as an example for the study during the period. The study aims to investigate the root causes of Muslim Turcophobia and to draw the attention of researchers to the issue in the context of two missionary writers (George Horton (d. 1942), Sir Edwin Pears (d. 1919)) who insulted, slandered, and attacked Muslims and saw Muslims as a threat to Christianity in the Turkish nation.